Fitness, Physical Activity and Health Practices of Grade 9 Students of Public High Schools of Botolan District Sy 2017-2018 - Romanban, Danica Corum; Gutierrez, Marilyn M. (Future Science / FSH-PH Publications, 2022)
This study aimed to determine the fitness, physical activity and health practices of Grade 9 students of public high schools of Botolan District, Division of Zambales during SY 2017-2018. The study utilized descriptive research design with questionnaire as the main instrument ingathering data from Grade 9 student-respondents who were randomly selected from six secondary schools in Botolan District. The students’ profiles considered in the study were limited to their age, sex, height, weight, body mass index, monthly family income, participation in organized sports, participation in unorganized physical activity and physical activities, leisure time and diet. The extent of preference of the respondents on fitness, physical activity and health practices were assessed in terms of physical activity as maximum health benefit and distinct types of physical activity to address unique health concerns and contribute in distinct ways to children’s health, health- and performance-related fitness. The study revealed that the majority respondents were female in their early teen- age hood, with average height, weight, normal body mass index and inadequate family monthly income. The respondents assessed “negative” for both organized and unorganized sports activities. The respondents assessed “often” with moderate physical activities, with 15-30 minutes moving a day and medium in the conduct of aerobic or Zumba while “agree” on the health practices. The respondents perceived “agree” on the overall general knowledge and awareness on fitness, physical activity and health practices. There is a significant difference between the organized and unorganized sports activity. There is a significant difference when grouped according to age, body mass index and family income respectively towards physical activity and health practices while significant on body mass index towards leisure time. There is significant difference when grouped according to height, weight, body mass index and family monthly income towards overall general knowledge and awareness on fitness, physical activity and health practices and there is a high positive relationship between the level of awareness and the level of sports participation Based on summary of the investigation conducted and the conclusions arrived at, the researcher have offered the following recommendations to consider healthy body a great treasure and to start engaging in physical activities that help and regulate good sound and healthy body instead of engaging in activities as drinking liquor or smoking that may cause severe illness or death; to encourage the respondents not to skip meals for better life and healthy body; to seek advises from health professionals or medical doctors before engaging in heavy sports activities; to assure rendering from gradual to complex physical activities; that a physically fit person eating a nutritionally adequate diet can have improved performance in school; to improve quality of life, one must practice and observe healthy living; and finally to conduct a parallel or similar study with in-depth and broader scope so as to validate and confirm the findings obtained in the study.